The Financial Performance of Merged and Acquired Firms: Energy and Consumer Sectors in Indonesia - Christopher Bradley Budiono; Nathania Cherryl Prayogo; Rachel Cintantya Hapsari; Nanik Linawati (JAFFA, 2024)
This research examines the difference in average financial performance one year before and after mergers and acquisitions in the energy and consumer sectors of public companies listed on the Indonesia Stock Exchange. The research sample consisted of 20 energy and 20 consumer sector companies that performed mergers and acquisitions from 2017 to 2021. Data processing was carried out using Paired Sample T-Test with the help of SPSS version 26. The research results showed an increase in the market prospect, leverage, and efficiency ratios one year after mergers and acquisitions in energy and consumer goods sector companies. Meanwhile, there was a decline in profitability and liquidity ratios one year after mergers and acquisitions in companies in the energy and consumer goods sectors. The result confirms that mergers and acquisitions contribute to differences in the financial performance of companies acquiring Indonesia’s energy and consumer goods sectors.